Efficacy of Phenylephrine and Ephedrine for Treatment of Hypotension Encountered During Caesarean Section - Leghari, Khursheed Hassan; Ahmed, Usman; Hussain, Aftab; Munir, Ali Arslan; Rana, Sumbal; Razzaq, Sajid (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the efficacy of Phenylephrine and Ephedrine in treating hypotension encountered during spinal anaesthesia for caesarean section. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Anaesthesia, Combined Military Hospital, Rawlakot Pakistan, from Sept 2020 to Aug 2021. Methodology: Hundred (50 in each Group) patients were observed. All patients were preloaded with 15ml/kg Hartmann’s solution ten minutes before giving spinal anaesthesia. Baseline blood pressure was recorded just before administration of spinal anaesthesia, at 1-minute intervals up to 5 minutes, and then every 5 minutes afterwards. When hypotension developed, vasopressors were administered, and blood pressure was noted every minute for three minutes following drug administration. The spinal block using 2ml of 0.75% hyperbaric bupivacaine was given at L3-L4 interspace with a 27G spinal needle (Quinke). Group-E patients were given 5mg bolus injection of Ephedrine if mean arterial pressure fell below 20% from baseline. Group-P patients were given a 50ug bolus of Phenylephrine if mean arterial pressure fell below 20% from baseline. Results: Demographic data was comparable in both groups. There was an insignificant difference between Phenylephrine and Ephedrine in terms of treating hypotension, with a p-value of 0.249. Ephedrine was effective in 41(82%) patients and was not effective in 9(18%) patients, whereas Phenylephrine was effective in 45(90%) patients and was not effective in 5(10%) patients. Conclusion: Our study concluded that Phenylephrine and Ephedrine are equally effective for treating hypotension encountered during spinal anaesthesia.